Genotoxicity and repeated-dose toxicity evaluation of dried Wolffia globosa Mankai. (2020) - Kawamata, Yasuko; Shibui, Yusuke; Takumi, Asuka; Seki, Takuya; Shimada, Tomoko; Hashimoto, Masaki; Inoue, Naohiko; Kobayashi, Hisamine; Narita, Takahiro
Highlights: Wolffia globosa Mankai can serve as a plant substitute for animal protein. Genotoxicity and subchronic toxicity studies (GLP) of dry Mankai were conducted. Dry Mankai was judged as having no potential to induce gene mutations in Ames test. Dry Mankai did not induce chromosomal aberration in in vitro micronucleus test. The NOAEL of Dry Mankai in 90-day dietary toxicity study was 20 % (w/w). Abstract: Wolffia is a genus of protein-rich aquatic plants. Mankai, a cultivated strain of Wolffia globosa, contains more than 40 % protein based on dry matter evaluation. Furthermore, Mankai is nutritionally excellent as a food material, and is expected to be applicable to various products as a substitute for animal protein. A battery of toxicological studies was conducted on the dried product of Mankai (Dry Mankai), with the expectation to utilize it as a raw material for food applications. Dry Mankai was not genotoxic in a bacterial reverse mutation test and in vitro micronucleus assay. In the subchronic toxicity study, rats were provided Dry Mankai in the diet at levels of 0 %, 5 %, 10 %, or 20 % (w/w), equivalent to 0, 3.18, 6.49, and 13.16 g/kg/day for males and 0, 3.58, 7.42, and 15.03 g/kg/day for females, respectively. No adverse effects that could be attributable to treatment were observed in clinical observations, body weight, food consumption, ophthalmology, hematology and blood chemistry, urinalysis, and macroscopic and microscopic findings. According to the repeated-dose study in rats, the no observed adverse effect level of Dry Mankai was 20 % (w/w) for both sexes (13.16 and 15.03 g/kg/day for males and females, respectively).